Serial Systemic Candida albicans Infection Highlighted by Proteomics - Arita, Glaucia Sayuri; Meneguello, Jean Eduardo; Sakita, Karina Mayumi; Faria, Daniella Renata; Pilau, Eduardo Jorge; Ghiraldi-Lopes, Luciana Dias; Campanerut-Sá, Paula Aline Zanetti; Kioshima, Érika Seki; Bonfim-Mendonça, Patrícia de Souza; Svidzinski, Terezinha Inez Estivalet (Frontiers in Cellular and Infection Microbiology, 2019)
Candida albicans is the major pathogen isolated from nosocomial bloodstream infections, leading to higher mortality rates. Thus, due to its clinical relevance, studies aiming to understand host–pathogen interactions in C. albicans infection are necessary. Therefore, we performed proteomic analysis using a murine model of serial systemic infection by C. albicans to evaluate possible changes in the protein profile of the pathogen over time. Firstly, we observed a reduction in the median survival time of infected animals with increasing passage number, suggesting a higher pathogenicity acquired during repeated infections. By LC-MS/MS, it was possible to obtain protein profiles from the wild-type strain (WT) and compare them to proteins extracted from Candida cells recovered from infected tissues during passages one, three, and four (P1, P3, and P4). We obtained 56, 29, and 97 proteins in P1, P3, P4, respectively, all varying in abundance. Regarding biological processes, the majority of proteins were related to carbohydrate metabolism, stress responses and amino acid metabolism. The proteins were also categorized according to their potentials role in virulence traits such as biofilm production, yeast-to-hyphae transition, phenotypic switching, proteins related to stress responses, and uncharacterized proteins. Therefore, serial infection in combination with as proteomic approach enabled us to deepen the existing knowledge about host-pathogen interactions.